Influence of Hydroxyl Group on IR Transparency of Tellurite‐Based Glasses. (10th December 2013) - Guery, Guillaume; Cardinal, Thierry; Fargues, Alexandre; Rodriguez, Vincent; Dussauze, Marc; Cavagnat, Dominique; Thomas, Philippe; Cornette, Julie; Wachtel, Peter; Musgraves, John David; Richardson, Kathleen
<x xml:space="preserve">Abstract</x> A study of the glass properties with two opposite levels of hydroxyl content is presented for two different tellurite glass families with molar composition 70TeO2‐10Bi2O3‐20ZnO and 80TeO2‐20Nb2O5. We show that melting tellurite‐based glasses in a dried‐oxidant atmosphere (relative humidity <1%) reduces drastically the OH impurities. The effect of reducing the OH content on the glass properties such as characteristic temperatures, crystallization stability (ΔT), density, and microhardness is investigated.